The Use of Computational Tools to Investigate the Impact of SARS-CoV2 Spike Protein Variants on Human Antibodies - Alencar, Sérgio Amorim de; Campoe, Rickson Passos; Rezende, Yasmin; Souza, Rute Pereira de (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
Understanding the process of formation of the complexes between Spike protein variants that make up the structure of the SARS-CoV2 virus and human antibodies, brings light into how variations have an impact on this complex formation. In this work, databases such as CoV3D, PDB and pyDockWEB were used to collect sequencing results and structures of SARS-CoV2 variants. Finally, molecular docking was also used in order to predict the interaction between the virus' Spike protein and antibodies. These results were then made available on a website produced exclusively for public dissemination of these analyses. Among other answers, this work serves as a guideline for molecular docking studies of the interaction between Spike protein variants and human antibodies.